Preparation and characterization and tablettting properties of new cellulose cbased pharmaceutical aid - Vijay Kumar (2001)
A new cellulose-based tabletting excipient, hereinafter referred to as UICEL, has been developed by treating cellulose powder with an aqueous solution of sodium hydroxide (conc. 5N) and subsequently precipitating it with ethyl alcohol. UICEL is similar in structure to AvicelÂ® PH-102, a commercial direct compression excipient commonly referred to as microcrystalline cellulose (MCC). It, however, shows the cellulose II lattice, while AvicelÂ® PH-102 belongs to the cellulose I polymorphic form. As produced, UICEL consisted of a mixture of aggregated and non-aggregated ï¬bers. The degrees of polymerization (DP) and crystallinity (DC) of UICEL, determined by the viscosity and powder X-ray methods, were 189â€“207 and 47â€“58%, respectively. AvicelÂ® PH-102, by comparison, showed an aggregated structure with DP and DC values corresponding to 248 and 76.9%, respectively. Compared to AvicelÂ® PH-102, UICEL shows higher true density, bulk density, tap density, Carrâ€™s index and Hausner ratio values. The mean deformation pressure (Py) values calculated from the linear portion of the Heckel plots for UICEL and AvicelÂ® PH-102 were about 104 and 87 MPa, respectively, suggesting that UICEL is less ductile than AvicelÂ® PH-102. The hardness values of UICEL tablets increased nearly linearly with increasing compression pressures. Comparatively, AvicelÂ® PH-102 formed stronger tablets. Irrespective of the compression pressure used, all UICEL tablets disintegrated within 15 s, whereas AvicelÂ® PH-102 tablets of comparable strengths remained intact for over 12 h. In conclusion, the results show that UICEL can be used as a direct compression excipient, especially in the design and development of fast-disintegrating tablets. Â© 2002 Elsevier Science B.V. All rights reserved.